2008
DOI: 10.1002/adem.200800179
|View full text |Cite
|
Sign up to set email alerts
|

3D Powder Printing of β‐Tricalcium Phosphate Ceramics Using Different Strategies

Abstract: Custom made macroporous β‐tricalcium phosphate (β‐TCP) bone substitutes were fabricated using 3D powder printing comparing three different preparation strategies. Samples fabricated using a novel hydraulic cement setting reaction showed the best printing resolution and highest mechanical performance. This method is a significant step forward in producing β‐TCP monoliths by rapid prototyping and would decrease processing time for commercial fabrication due to their rapid hardening and ease of handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(102 citation statements)
references
References 24 publications
3
99
0
Order By: Relevance
“…Compared to that, the immersion in 7.5 wt.% LA showed a lower coverage. Literature claims a compressive strength of 3D-printed composites with other bio polymers in a range of 0.5-5 MPa [6] [7]. This emphasizes the potential of the herein investigated material with its 16.3 MPa CS.…”
Section: Discussionmentioning
confidence: 54%
“…Compared to that, the immersion in 7.5 wt.% LA showed a lower coverage. Literature claims a compressive strength of 3D-printed composites with other bio polymers in a range of 0.5-5 MPa [6] [7]. This emphasizes the potential of the herein investigated material with its 16.3 MPa CS.…”
Section: Discussionmentioning
confidence: 54%
“…This is not fully understand and not in agreement with previous studies which however did not show relative cell growth, thus can not be directly compared. [21,25,51,52] Cytoskeleton evaluations showed that incorporation of both fillers improved its organization. In general, for the filled samples cytoskeleton was well organized with well developed actin and tubulin networks when compared with pure polymer samples.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] Concentrating on bone tissue applications and considering polymer based materials (filled polymers and composites), hydroxyapatite, tricalcium phosphate (TCP) or Bioglass are the most popular used fillers. [16,[19][20][21][22][23][24][25][26] Other interesting materials are phosphate glasses, which have readily tuneable properties to improve cellular activity [27][28][29][30][31] or inhibit biofilm formation (antimicrobial glasses). [32][33][34] To date they were rarely used as polymer fillers.…”
mentioning
confidence: 99%
“…One of the important benefits of this method is the powder bed support by itself for each successive layer. The fragility of the obtained parts is considered a drawback [81][82][83][84][85][86][87][88].…”
Section: D Printing (3dp)mentioning
confidence: 99%